Enhanced economic benefit of recycling Fe3O4 for promotion of volatile fatty acids production in anaerobic fermentation of food waste. (February 2023) - Wang, Lanting; Liu, Tianxiao; Xu, Jing; Wang, Zhiwei; Lei, Zhongfang; Shimizu, Kazuya; Zhang, Zhenya; Yuan, Tian
Graphical abstract: Highlights: No study explored the feasibility of Fe3 O4 recycling on VFAs enhancement from FW. Economic analysis was first conducted based on actual recycle performance of Fe3 O4 . Recycled Fe3 O4 for once and twice could largely enhance VFAs production by 17%. Kinetic and XRD analysis further confirmed the feasibility of Fe3 O4 recycling. 13-fold higher net profit can be achieved by recycling Fe3 O4 for VFAs production. Abstract: Fe3 O4 addition in anaerobic fermentation of food waste (FW) is promising for enhancing volatile fatty acids (VFAs) production. However, the large amount of Fe3 O4 in the digestate fertilizer leads to the waste of resources and possible toxicity to organisms. Thus, this study investigated the feasibility of Fe3 O4 recycling for VFAs enhancement in anaerobic fermentation of FW and performed the cost-benefit evaluation of this process. Results revealed that Fe3 O4 could be successfully recycled twice with recovery rates of 71.5% and 65.5%, respectively. X-ray diffraction analysis revealed a slight change to the Fe2 O3 -like structure after 2-time recycling. The VFAs yields were enhanced by 17.2% and 17.0% in Cycles 1 and 2 owing to the enhanced activities of hydrolytic and acid-forming enzymes. The net income of the Fe3 O4 recycling process was about 13-fold higher than that of the conventional treatment process, suggesting a promising and economically feasible strategy for enhancing VFAs production.